Simple Two-step Chromatographic Method for Purification of Ovomacroglobulin - Geng, Fang; Huang, Xi; Ma, Mei-Hu; Li, Zhi; Zhang, Xiao-Wei (Asian Journal of Chemistry, 2012)
Ovomacroglobulin, also known as ovostatin, has been demonstrated to possess broad-spectrum inhibitory activity against various types of proteases and some other important biological activities, such as inhibiting sepsis, accelerate wound healing and antiinflammatory. In this study, an improved method was developed to purify ovomacroglobulin. Ovomacroglobulin-rich part obtained from polyethylene glycol precipitation (4-8 %) was separated by using Q Sepharose Fast Flow anion-exchange chromatography and then Sephacryl S-200 was employed to the purification of ovomacroglobulin. The recovery of the whole process was 37.76 %, the obtained protein was identified as ovostatin/ovomacroglobulin (Gallus gallus) by LC-ESI-LTQ. This procedure has an advantage in rapid preparation of ovomacroglobulin with a higher recovery.